Technology and Application of High-Capacity USIM Card - Shuanghe Dong; Binfeng Yan; Bo Hu; Xiaohua Guo (Dianxin kexue)
Abstract: A new high-capacity USIM card was introduced and discussed in detail and depth. Its key technology （IC-USB interface, integrated NAND flash chips）was introduced. Compared to traditional SIM card, the high-capacity USIM card has higher transmission rates, larger storage space, and data security storage. The structure and functions of supporting client and management platform were discussed. The influence of this technology may have caused was analyzed.Appropriate suggestions and plantings to the future of business model and application scenario were given.